PRAGMATIC ANALYSIS OF THE EXPRESSION OF THE CONCEPT OF REPRIMAND IN UZBEK AND ENGLISH THROUGH PARALINGUISTIC MEANS - Ataboyev Isroiljon Mirza o‘g‘li (Sciental Journals Publishing, 2025)
This article analyzes the pragmatic characteristics of how reprimanding speech acts are expressed through paralinguistic means in Uzbek and English. Paralinguistic tools are non-verbal yet meaning-enhancing elements that reflect the speaker’s emotional state, social position, and communicative intent in accordance with the context. The paper examines the phonatory, kinesics, and graphic (paragraphemic) aspects of these tools and explores their culturally specific usage in both English and Uzbek. Examples are used to compare social-emotional expression tools unique to each language, and to demonstrate how the pragmatic impact of a reprimand can be intensified through paralinguistic means.
Keywords: Reprimand, paralinguistic, pragmatics, phonation, paragraphemic, kinesics, context, sociolinguistic specificity.